Ilmu Pengetahuan dan Teknologi dalam Kehidupan Manusia: Sebuah Tinjauan dalam Perspektif Filsafat - Nurazizah, Tsani Shofiah; Ulfiah, Zakiah; Herlambang, Yusuf Tri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to elucidate the philosophy of technology regarding the role of science and technology in human life. The research method employed is qualitative descriptive with a literature study approach. Data collection in this study is by looking for data from various library sources such as research reports, journal articles, theses, dissertations, books, and other scientific articles. Study, analyze, and relate relevant literature to the problem to be researched and solved, then use it to present data, reduce data, and ultimately draw conclusions. The findings of this research indicate that the role of science and technology (IPTEK) is very diverse in human life, involving aspects such as the utilization of natural resources, influence on human life, and impact on social change. Based on the research results, it can be concluded that the role of science and technology in human life from the perspective of the philosophy of science and technology is extensive. The way humans interact with the world, work, and live daily is significantly influenced by technological and scientific advancements